Establishing Infinite Methods of Construction of Magic Squares - Miranda, Lohans de Oliveira; Miranda, Lossian Barbosa Bacelar (Journal of Nepal Mathematical Society, 2021)
Here we have established infinite methods of building doubly even magic squares from doubly even magic squares of n order (n ≥ 20) which are formed by blocks of order four whose sums of elements of lines, columns and diagonals are all equal at 2n2 + 2. Such a characteristic of these special magic squares causes a large production of other magic squares.